Optimization of parameters of laser non-linear inclined cutting on stainless steel metal - Abbas, Abbas Allawi (2014)
The aim of this research is to develop a laser cutting process model that can predict the relationship between the process input parameters and resultant surface roughness; kerf width characteristics. The research conduct is based on the Design of Experiment (DOE) analysis. Response Surface Methodology (RSM) is used in this research, it is one of the most practical and most effective techniques to develop a process model. Even though RSM has been used for the optimisation of the laser process, published RSM modelling work on the application of laser cutting process on cutting material is lacking. This research investigates laser cutting stainless steel to be best the circumstances laser cutting using RSM process. The input parameters evaluated are gas pressure, power supply and cutting speed, the output responses being kerf width, surface roughness. The laser cutting process is one of the widely used techniques to cut thickness material for various applications such as fiber, steel wood fabrication. In the area of laser cutting material,it can be improved drastically with the application of hard cutting. The application of cut on stainless steel for various machining techniques, such as bevel linear and bevel non-linear cutting, requires different cut characteristics, these being highly dependent on the process parameters under which they were formed. To efficiently optimize and customize the kerf width and surface roughness characteristics, a machine laser cutting process model using RSM methodology was proposed.